New rodents (Mammalia) from the late Oligocene of Cabeza Blanca (Chubut) and the first rodent radiation in Patagonia - Vucetich, Maria Guiomar (2014)
Caviomorph rodents, the New World Hystricognathi, are one of the most characteristic groups of South American mammals. Although they have been in the continent at least since the middle Eocene, those of the Deseadan Land mammal Age (early–late Oligocene) are the best source to understanding their early history due of their good record, large geographic distribution and good temporal calibration of many of the local faunas. Here, we describe the following new taxa from the classical locality of Cabeza Blanca: Octodontoidea Acaremyidae Galileomys baiosn. sp., Octodontoidea incertae sedis Ethelomys loomisin. gen.,n. comb., Acarechimys leucotheaen. sp., Protacaremys? adilosn. sp., Chinchilloidea incertae sedis Loncolicu tretosn. gen., n. sp., Incamys menniorumn. sp., Caviomorpha incertae sedis Llitun notucan. gen., n. sp., Leucokephalos zeffiaen. gen., n. sp. and Cephalomyidae Cephalomys ceciaen. sp. The DP4 of an ‘eocardiid’, Asteromys punctus? is described for the first time. These new taxa allow us to reinterpret the relationships of some of the previously known Deseadan species and genera. They show a great early diversification at least for extra Andean Patagonia, involving at least three of the main caviomorph lineages: octodontoids, chinchilloids and cavioids.